(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Hypoglycemia and recurrent hypoglycemia may be associated with a significant increase in the risk of major macrovascular and microvascular events and recurrent hypoglycemia was associated with arise in mortality, morbidity. The objectives of this study are to estimate the prevalence of hypoglycemic episodes in T2DM patients attending the National Center for Diabetes, Endocrinology and Genetics and to estimate the rate of hypoglycemic unawareness in these patients and to determine the risk factors associated with hypoglycemic episodes. Across-sectional study was carried out at the National Center for Diabetes ,Endocrinology and Genetics (NCDEG) in Amman-Jordan, conducted from1st of November 2012 to 1st of March 2013 .A total of 1055 patients with type 2 diabetes according to (ADA) and on one or more hypoglycemic agents .Data collected on the severity and frequency and symptoms of hypoglycemic episodes in the 3 month prior to enrollment based (Hypoglycemic Health Assoc. of Australia Questionnaire). of 1055patients with type 2 diabetes mellitus who aged between 21-85years 499males 47.3% and 556 females 52.7%,25.6%had controlled HBA1c, 67.7%were on insulin treatment, 39.8%of them are having type 2 DM for more than 10 years, 57.7% of them were obese with a mean (SD)of the BMI 31.2kg/m2(4.9).Prevalence of hypoglycemia was 46.6% for patients with hypoglycemic symptoms .Logestic regression analysis revealed that occupation, duration of diabetes , HBA1C level , diabetic nephropathy, diabetic foot and type of medication were significant correlated with hypoglycemic episodes . Hypoglycemia is common among Jordanian patients with type 2 DM attending the NCDEG, to maintain glycemic control and prevent hypoglycemia attack should be designed schedule for education concerning self monitoring of blood glucose, diet, medication, and lifestyle. Encourage patients to treat hypoglycemia episodes if showed immediately and don’t delay in treating hypoglycemia.